Efficacy of sedation with dexmedetomidine plus propofol during esophageal endoscopic submucosal dissection. Issue 7 (4th February 2021) - Ashikari, Keiichi; Nonaka, Takashi; Higurashi, Takuma; Takatsu, Tomohiro; Yoshihara, Tsutomu; Misawa, Noboru; Arimoto, Jun; Kanoshima, Kenji; Matsuura, Tetsuya; Fuyuki, Akiko; Ohkubo, Hidenori; Chiba, Hideyuki; et al.
Abstract: Background and Aim: During endoscopic submucosal dissection for superficial esophageal cancer, patient body movement can sometimes occur, which may cause discontinuation of the procedure. Propofol and dexmedetomidine have recently been found to be useful sedatives for endoscopic submucosal dissection. This study investigated whether sedation using propofol plus dexmedetomidine can suppress the patient's body movements during esophageal endoscopic submucosal dissection and compared this combination with sedation using propofol alone. Methods: This was a prospective double‐blind randomized controlled trial. Patients with superficial esophageal cancers who underwent esophageal endoscopic submucosal dissection at Yokohama City University Hospital were prospectively enrolled and were randomly assigned to the propofol and the propofol plus dexmedetomidine groups. The primary endpoint was the incidence of restlessness. The secondary endpoints were the satisfaction score, maintenance dose of propofol, and number of rescue propofol injections. Results: Sixty‐six patients (propofol group: n  = 33; combination group: n  = 33) were included. The combination group had a significantly lower incidence of restlessness than the propofol group (3.0% vs 27.3%, P  = 0.02). In the combination group, the satisfaction scores of the endoscopists were significantly higher, the maintenance dose of propofol was significantly lower, and the number of rescue propofol injections was lower than those in the propofol group (3.0% vs 18.2%, P  < 0.001). Although the incidence of bradycardia was significantly higher in the combination group (30.3% vs 3.0%, P  < 0.01), no serious adverse effects occurred. Conclusion: The propofol plus dexmedetomidine combination provided excellent sedation that effectively suppressed the patient's body movements during esophageal endoscopic submucosal dissection.